2014
DOI: 10.4293/jsls.2014.00393
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Office Hysteroscopy for Abnormal Uterine Bleeding

Abstract: Background and Objectives:Office diagnostic hysteroscopy allows physicians to directly view the endometrial cavity, tubal ostia, and endocervical canal without taking the patient to the operating room (OR). We sought to determine whether office hysteroscopy performed to evaluate abnormal uterine bleeding decreases the need for hysteroscopy performed in the OR and the associated financial and risk implications.Methods:One hundred thirty patients who underwent office diagnostic hysteroscopy between January 2009 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 13 publications
1
34
0
3
Order By: Relevance
“…Hysteroscopy plays a crucial role in the evaluation of the uterine cavity in women with abnormal uterine bleeding and infertility, and evolution in both the procedure itself and the instrument has enabled its use in the office context . As an office procedure, it gives comparable results to inpatient hysteroscopy, with the advantages of lower costs and avoidance of anesthetic risks …”
Section: Introductionmentioning
confidence: 99%
“…Hysteroscopy plays a crucial role in the evaluation of the uterine cavity in women with abnormal uterine bleeding and infertility, and evolution in both the procedure itself and the instrument has enabled its use in the office context . As an office procedure, it gives comparable results to inpatient hysteroscopy, with the advantages of lower costs and avoidance of anesthetic risks …”
Section: Introductionmentioning
confidence: 99%
“…Hysteroscopy is currently the most informative investigation for women with abnormal uterine bleeding and uterine factor infertility . Outpatient hysteroscopy is comparable with surgical inpatient hysteroscopy but offers reduced anaesthesia risks and decreased overall costs . It involves the use of miniaturised endoscopic equipment to directly visualise the endometrial cavity without the need for formal operating room facilities or anaesthesia …”
Section: Introductionmentioning
confidence: 99%
“…Outpatient hysteroscopy has been shown to be safe and acceptable to women. Research has shown that the outpatient approach is more cost-effective, and patients value the convenience of an immediate diagnosis [9,10]. This allows women to be counselled about their treatment options, thus avoiding lengthy follow-up appointments.…”
Section: Introductionmentioning
confidence: 97%